2022
DOI: 10.1177/10778012221137921
|View full text |Cite
|
Sign up to set email alerts
|

Why Young Women Who Use Opioids Are at Risk for Rape: The Impact of Social Vulnerabilities and Sexually Coercive Drug Using Contexts

Abstract: This study tests a theoretically informed model to understand why women who use opioids (WWUO) are at risk of rape while using drugs. Structured interviews were conducted with 168 WWUO. Three domains were hypothesized to increase risk: the sexually coercive context of drug use, women's social vulnerability, and drug use severity. Logistic regression examined the odds of being raped by domain. One-third of WWUO had been raped while using drugs. The sexually coercive context and social vulnerability domains sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…Women had more negative thoughts about drug addiction than men. These results were consistent with previous studies reporting the effects of heightened vigilance due to women’s vulnerability to drug problems [ 41 ]; women disabled by drug use are physically more vulnerable than men and are more likely to be targeted when exposed to crime [ 42 ]; woman drug addicts are exposed to an exploitative environment [ 43 ], and the effects of drugs can affect women’s defensive behavior to protect themselves and their ability to actively express themselves [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Women had more negative thoughts about drug addiction than men. These results were consistent with previous studies reporting the effects of heightened vigilance due to women’s vulnerability to drug problems [ 41 ]; women disabled by drug use are physically more vulnerable than men and are more likely to be targeted when exposed to crime [ 42 ]; woman drug addicts are exposed to an exploitative environment [ 43 ], and the effects of drugs can affect women’s defensive behavior to protect themselves and their ability to actively express themselves [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Women had more negative thoughts about drug addiction than men. These results were consistent with previous studies reporting the effects of heightened vigilance due to women's vulnerability to drug problems; 41 women disabled by drug use are physically more vulnerable than men and are more likely to be targeted when exposed to crime; 42 woman drug addicts are exposed to an exploitative environment, 43 and the effects of drugs can affect women's defensive behavior to protect themselves and their ability to actively express themselves. 44 In this study, it was found that those who thought that they should receive active counseling or hospital treatment when suffering from opioids and drug abuse were more likely to agree to stigmatization than those who tried to solve it personally.…”
Section: Discussionsupporting
confidence: 91%
“…This study is significant because gender violence is considered a key source of inequality when addressing the treatment of drug addiction in women (Jessell et al, 2022) and it has been shown that gender violence has multiple bidirectional relationships with drugabuse related problems which should be addressed together (James et al, 2004;Lorvick et al, 2014).…”
Section: Purpose Of the Studymentioning
confidence: 99%